Impact of multivessel disease on reperfusion success and clinical outcomes in patients undergoing primary percutaneous coronary intervention for acute myocardial infarction - Sorajja, Paul; Gersh, Bernard J; Cox, David A; McLaughlin, Michael G; Zimetbaum, Peter; Costantini, Costantino; Stuckey, Thomas; Tcheng, James E; Mehran, Roxana; Lansky, Alexandra J; Grines, Cindy L; Stone, Gregg W (European heart journal, 2007)
We sought to investigate the impact of multivessel coronary artery disease (CAD) on reperfusion success and prognosis following primary percutaneous coronary intervention (PCI) in patients with acute myocardial infarction (AMI). The influence of multivessel disease on myocardial reperfusion and subsequent survival after primary PCI has not been studied. In the CADILLAC trial, primary PCI was performed in 2082 patients of any age with AMI within 12 h of symptom onset. Myocardial perfusion post-PCI assessed by ST-segment recovery and myocardial blush and clinical outcomes were stratified by the extent of CAD. Single-, double-, and triple-vessel disease were present in 1066 (51.2%), 692 (33.2%), and 324 (15.6%) patients, respectively. Patients with multivessel disease compared with those with single-vessel disease undergoing primary PCI were significantly more likely to have absent ST-segment recovery (13.3 vs. 7.4%, P = 0.01), though the rates of post-procedural TIMI-3 flow (89.7 vs. 88.9%, P = 0.66) and grade 2 or 3 myocardial blush (51.2 vs. 51.5%, P = 0.91) in the infarct vessel were comparable. By 1 year, the cumulative incidence of death for patients with single-, double-, and triple-vessel disease was 3.2, 4.4, and 7.8%, respectively (P = 0.003), and the composite rate of major adverse cardiac events (MACE) was 14.8, 19.5, and 23.6%, respectively (P = 0.0006). By multivariable analysis, the presence of triple-vessel disease was the strongest predictor of 1-year death [hazard ratio (HR) = 2.60, P = 0.009], death and re-infarction (HR = 1.88, P = 0.03), and MACE (HR = 1.80, P = 0.0009). Patients with extensive CAD in vessels remote from the infarct-related artery have reduced reperfusion success and an adverse prognosis following primary PCI in AMI. Future studies regarding the optimal treatment of patients with multivessel disease and AMI are warranted.